2021
DOI: 10.1108/jd-04-2021-0087
|View full text |Cite
|
Sign up to set email alerts
|

“Data stickiness” in interagency government data sharing: a case study

Abstract: PurposeThe provision of high-quality e-Government services requires efficient and collaborative sharing of data across varied types of government agencies. However, interagency government data sharing (IDS) is not always spontaneous, active and unconditional. Adopting a stickiness theory, this paper reports on a research study, which explores the causes of data stickiness in IDS.Design/methodology/approachThis study employed an inductive case study approach. Twenty-three officials from the government of City M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…While these examples concern cross-border information exchange, Zhou et al (2021) also identified considerable challenges in data exchange between agencies at different levels of government within China, with inter-relationships between agencies proving to be paramount. This is an important consideration for internal border control systems in a federated country such as Australia where information exchange between federal immigration authorities and criminal justice agencies operated by states and territories is crucial.…”
Section: Developments In Automated Governancementioning
confidence: 99%
See 1 more Smart Citation
“…While these examples concern cross-border information exchange, Zhou et al (2021) also identified considerable challenges in data exchange between agencies at different levels of government within China, with inter-relationships between agencies proving to be paramount. This is an important consideration for internal border control systems in a federated country such as Australia where information exchange between federal immigration authorities and criminal justice agencies operated by states and territories is crucial.…”
Section: Developments In Automated Governancementioning
confidence: 99%
“…Data sharing between government agencies often forms the 'bedrock' for digital government (Zhou et al, 2021(Zhou et al, , p. 1286. While the language used around technological developments often conveys an impression of unimpeded integration across electronic systems, the reality is often otherwise, and the smooth flow of data between agencies is far from straightforward or guaranteed.…”
Section: Developments In Automated Governancementioning
confidence: 99%